IMPLEMENTASI KEBIJAKAN REFOCUSING ANGGARAN PENANGGULANGAN COVID -19 DI KABUPATEN NIAS SELATAN - MANURUNG, JULIANA ERNAWATI; SILABAN, PASAMAN; HUTAHAEAN, MARLAN (JURNAL ILMIAH KOHESI, 2022)
Covid-19 is an event or phenomenon that rarely occurs, its impact not only affects human health but also greatly involves the world economy imbalances, namely in Indonesia and South Nias Regency in particular. The South Nias Government followed instructions from the administrative center to refocus the budget on dealing with COVID-19. In implementing the Covid-19 policy in South Nias, the local bureaucracy (Indonesian: Organisasi Perangkat Desa (OPD)) follows the direction and government policies, especially for cutting the local government budget (OPD). This research was qualitative research in which data was taken by using the observation method, observing documents, and interviews with informants who have a relationship with budget policy. Hence, the study showed that with the policies carried out by the South Nias government, beneficiaries were greatly helped and could save on household expenses.